Hubungan Motivasi Belajar dengan Prestasi Belajar Siswa Kelas Tinggi - INA ATRIANA; Abd Hafid; Satriani, DH Satriani, DH (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2021)
The problem in this study is the low motivation of students to learn so that it makes students not enthusiastic in learning. This research is a descriptive quantitative research with a correlation model that aims to determine the relationship between learning motivation and high grade students' learning achievement. The results of this study indicate that there is a significant relationship between learning motivation and learning achievement of high-class students with tcount (9.4250) greater (>) ttable value (1.66365) which means H0 is rejected and H1 is accepted. Based on the analysis above, it can be concluded that student learning motivation has an impact on students' enthusiasm for learning in following the learning process so that they can improve their learning achievement. From these conclusions, the impact resulting from this study is known that high learning motivation can improve student achievement.